Accountability, corruption and democracy a clarification of concepts - Cariño, Ledivina V. (1991)
This article attempts to define accountability. The issue of accountability should not only be limited to the public sector but should also encompass the private sector. It also examines why corruption exists. Three meanings of corruption were suggested and the most appropriate definition is that which relates to public interest.
Keywords: Government accountability; Corruption -- Government policy; Political corruption